Isolation and purification of different high-purity cell populations from pig muscle tissue - Zenan Hu; Zheng Liu; Renpeng Guo; Shijie Ding; Guanghong Zhou (Food Materials Research)
Cultured meat technology is an emerging approach to meat production that generates edible meat tissue by cultivating animal-derived stem cells. Muscle stem cells (MuSCs) are essential seed cells for cultured meat production. However, due to the complexity of muscle tissue, obtaining highly pure MuSCs and maintaining their purity during passaging remains a significant challenge. Our research addressed the issue by reevaluating the cell sorting strategy for porcine MuSCs and other cell types. A new combination of markers—CD31, CD45, JAM1, ITGA5, and ITGA7—were introduced here, sorting the muscle mononuclear cells into three distinct groups. Immunofluorescence staining and RNA-sequencing indicated three distinct cell types—MuSCs, smooth muscle cells (SMCs), and fibro-adipogenic progenitors (FAPs)—each displayed high expression levels of their characteristic markers. Additionally, after successive passaging, MuSCs obtained through this refined approach exhibited higher cell purity and improved myogenic properties compared to previous methods. Overall, this study presents a method for simultaneously obtaining MuSCs, SMCs, and FAPs with high purity from porcine muscle tissue, providing a high-quality source of seed cells for cultured meat production.